Obesity- and lipid-related indices as a predictor of obesity metabolic syndrome in a national cohort study - Gui, Jiaofeng; Li, Yuqing; Liu, Haiyang; Guo, Lei-lei; Li, Jinlong; Lei, Yunxiao; Li, Xiaoping; Sun, Lu; Yang, Liu; Yuan, Ting; Wang, Congzhi; Zhang, Dongmei; et al. (Frontiers in Public Health, 2023)
Objective: Metabolic syndrome is common condition among middle-aged and elderly. Recent studies have reported the association between obesity-and lipid-related indices and metabolic syndrome, but whether those conditions could predict metabolic syndrome is still inconsistent in a few longitudinal studies. In our study, we aimed to predict metabolic syndrome by obesity-and lipid-related indices in mid-aged and elderly Chinese. Method: A national cohort study that consisted of 3640 adults ( ≥ 45years）was conducted. Thirteen obesity-and lipid-related indices, including body mass index (BMI), waist circumference (WC), waist-height ratio (WHtR), conicity index (CI), visceral adiposity index (VAI), Chinese visceral adiposity index (CVAI), lipid accumulation product (LAP), a body shape index (ABSI), body roundness index (BRI), triglyceride glucose index (TyG-index) and its correlation index (TyG-BMI, TyG-WC, TyG-WHtR) were recorded. Mets were defined based on the criteria of the National Cholesterol Education Program Adult Treatment Panel III (2005). Results: The thirteen obesity-and lipid-related indices were independently associated with MetS risk, even after adjustment for age, sex, educational status, history of smoking, taking activities, having regular exercises, and chronic diseases. The ROC analysis revealed that the twelve obesity- and lipid-related indices included in the study were able to discriminate MetS [area under the ROC curves (AUC > 0.6, P < 0.05)] and ABSI were not able to discriminate MetS [area under the ROC curves (AUC< 0.6, P > 0.05)]. The area under the curve (AUC) of TyG- BMI was the highest in men, and that of CVAI was the highest in women. Conclusion: Among middle-aged and older adults, all obesity-and lipid-related indices, except ABSI, were able to predict metabolic syndrome. In addition, in men, TyG-BMI is the best indicator to indicate metabolic syndrome, and in women, CVAI is considered the best hand to indicate metabolic syndrome. At same time, TyG-BMI, TyG-WC and TyG-WHtR performed better than BMI, WC, WHtR in predicting metabolic syndrome in both male and female. Therefore, the lipid-related index outperforms the obesity-related index in predicting metabolic syndrome. In addition to CVAI, LAP showed a good predictive correlation, even more closely than lipid-related factors in predicting metabolic syndrome in women.